FAKTOR-FAKTOR PENENTU INKLUSI KEUANGAN DI INDONESIA PERIODE TAHUN 2012-2016 - Yuni Noor Annisa; Sugeng Setyadi; Samsul Arifin (Tirtayasa Ekonomika, 2019)
This study aims to determine the effect of inflation, gross domestic product (GDP) per capita, Micro, Small and Medium Enterprises (MSMEs) and Non Performing Loans (NPL) on financial inclusion in Indonesia, with indicators of 33 provinces during the period of 2012-2016. The method used in processing data is the panel data. The results showed that the inflation variable have effect on financial inclusion, GDP per capita have effect on financial inclusion and the NPL have effect on financial inclusion in Indonesia for the period of 2012-2016. However, MSMEs have no effect on financial inclusion in Indonesia for the period of 2012-2016